2018
DOI: 10.1016/j.ijindorg.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A model of directed consumer search

Abstract: We present a framework to study directed consumer search. Firms sell products with two attributes. One is readily observable, the other is observed only after visiting a firm. Search is directed as the order of search is influenced by the observ-R We are very grateful to Régis Renault, the Editor, and two anonymous referees for their constructive comments and suggestions. Previous versions of this paper circulated as "Consumer Search with Observable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…is to show that this result holds in a more general environment by adopting the indirect approach explained above. As argued and explained in more detail by Haan, Moraga-González, and Petrikaite (2017), this result is consistent with some recent empirical findings. For example, Moraga-González, Sándor, and Wildenbeest (2015) structurally estimated a consumer search model using data from the Dutch automobile market, where price information is believed to be easily accessible, and found that reducing inspection costs led to higher prices for some car models.…”
Section: Related Literaturesupporting
confidence: 92%
See 4 more Smart Citations
“…is to show that this result holds in a more general environment by adopting the indirect approach explained above. As argued and explained in more detail by Haan, Moraga-González, and Petrikaite (2017), this result is consistent with some recent empirical findings. For example, Moraga-González, Sándor, and Wildenbeest (2015) structurally estimated a consumer search model using data from the Dutch automobile market, where price information is believed to be easily accessible, and found that reducing inspection costs led to higher prices for some car models.…”
Section: Related Literaturesupporting
confidence: 92%
“…As argued and explained in more detail by Haan, Moraga-González, and Petrikaite (2017), this result is consistent with some recent empirical findings. As argued and explained in more detail by Haan, Moraga-González, and Petrikaite (2017), this result is consistent with some recent empirical findings.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations